Implementation of Management Strategies to Improve Employee Performance at Rural Banks in East Java - Fauzan Muttaqiean; Retno Cahyaningati; Ria Meilan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2023)
The purpose of this research is to find out the importance of implementing management strategies to improve the performance of employees of Rural Banks in East Java. The limitation of the problem is aimed at decision-making human resources at BPRs in East Java, namely commissioners and directors as information sources. Problem solving is done by interactive analysis which includes data collection, data reduction, data presentation, and verification. In this research, the research team prepared questionnaires for interviewees and the results were used for descriptive analysis of employee performance at PT. Rural Banks in East Java. It can be concluded that the management strategy carried out by BPR management, is the approach of humanism, organizational justice, and spiritual leadership, and Organizational Citizenship Behavior as indicators of the process towards optimizing the performance of BPR human resources. All employees are given opportunities proportionally to develop themselves and are involved in the development of employee human resources which are assets and human capital in the company. In general, BPR governance has implemented the principles of Good Corporate Governance.